On the Conharmonic Curvature Tensor of Generalized Sasakian-Space-Forms. (25th December 2012) - De, U. C.; Singh, R. N.; Pandey, Shravan K.
Abstract : The object of the present paper is to characterize generalized Sasakian-space-forms satisfying certain curvature conditions on conharmonic curvature tensor. In this paper we study conharmonically semisymmetric, conharmonically flat, ξ -conharmonically flat, and conharmonically recurrent generalized Sasakian-space-forms. Also generalized Sasakian-space-forms satisfying C · S = 0 and C · R = 0 have been studied.